The primary structure of histone H2B from the mollusc Patella granatina - Van Helden, Paul David (Department of Molecular and Cell Biology, 2023)
Histones H2B were isolated from the gonads of a mollusc (Patella granatina) and from chicken (Gallus domesticus), crocodile (Crocodylus niloticus) and amphibian (Xenopus laevis) erythrocytes. The H2B's were purified by ion-exchange and gel exclusion chromatography. The complete primary structure of the mollusc hi stone H2B t 11 has been deduced from the sequences established of pa e a adjoining and overlapping peptides by the Edman degradation procedure. The partial structure of H2B from chicken erythrocytes (87 residues), crocodile erythrocytes (75 residues) and Xenopus erythrocytes (63 residues) was also established. The amino acid sequences are compared to those of other histones H2B. The effect of mutations on the predicted secondary structure of histone H2B is considered.